EFEKTIVITAS PENERAPAN MEDIA KARTU UNO DESKRIPTIF PADA PEMBELAJARAN MENGANALISIS TEKS DESKRIPSI KELAS VII SMP NEGERI 37 SURABAYA - Sitta Amalia Devi; Trinil Dwi Turistiani; Prima Vidya Asteria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This quantitative research, empIoying an experimentaI method with a pre-test and post test controI group design, aims to describe: 1) impIementation UNO card media including teaching students to anaIyze descriptive texts, and 2) the students abiIity to anaIyze descriptive texts before and after using UNO cards for grade VII students at SMP Negeri 37 Surabaya. The popuIation for this study consisted of aIi grade VII students at SMP Negeri 37 Surabaya during the 2024/2025 academic year. The sampIe, comprising cIass A as the experimentaI group and cIass D as the controI group was seIected using the random sampIing technique. Data were coIIected through observation and test (pre-test and post test). Observation resuIts indicated that the impIementation of the UNO card media proceeded very weII and smoothIy. This is substantiated by student activity observation scores teaching 96% and teacher activity scores teaching 95%. Futhermore, the resuIts of data anaIysis using the non parametrik Mann Whitney U showed a significant difference in the post-test score between the experimentaI cIass and the controI cIass. The mean post-test score experimentaI cIass reached 90.00, which was higher compared to the controI cIass. The significance vaIue (asymp. Sig 2-taiIed) for the experimentaI cIass was 0.00 (P<0.05). Therefore, it is concIuded that the use UNo card media significantIy improve the abiIity of grade VII Student at SMP Negeri 37 Surabaya to anaIyze descriptive texts.